Establishing A Partnership With the Local Population in Resolving the Problems in Solid Domestic Waste Management - Dunayev, Ihor; ZyuzOlʹha (Pressing Problems of Public Administration, 2019)
Today, creating an ef cient and sustainable solid waste management (SWM) system is seemed as a topical problem for Ukraine and all developing countries. Due to Ukrainian lack of infrastructure for waste disposal, as well as lack of culture of solid waste management and proper co- nancing, a de-facto setting almost effective mechanisms up for the public governance in a sphere of solid waste is rising as a need. With the advent of Ukraine’s independence, domestic politicians and local governance leaders annually declare their intentions to create an effective system of solid waste management at a local level. As not every citizen is willing to participate in public discussions but standing as a public representative, it’s reasonable to determine a rising population’s role in solid waste management. There is no single point of view among scientists as to what the role of population in solid waste management should be: on the one hand, the population naturally produces domestic waste, but on the other, the population is capable to minimize the waste generation process and to improve its attitude towards it. So a question arises: how to achieve the minimization of SWM and to maximize population’s involvement in? For this purpose it is necessary to turn to a proper foreign experience. For a long time, Ukrainian scientists are used to not paying their attention enough to a problem of involving the population in domestic waste management, although the role of the population is usually considered in a separate waste collection, as a maximum. At the same time, more and more foreign academicians deeper consider the population’s participation in a decision-making in SWM in the context of impacting on some other subjects and formatting a right culture of solid waste treatment. Theoretical background of public management of solid waste was highlighted in numerous papers of A. Marzuki, A. Maiyaki, R. Mustafa and others. The forms of population‘s participation in the SWM were also studied by K. Garnett, T. Cooper, P. Longhurst, F. Trimurni, and others. Despite the progressive experience in attracting the population to the SWM, this problem is not suf ciently articulated and explored in present-day Ukraine, so, it’s an actual issue to rethink possibilities to involve citizens in the SWM process taking into account proper foreign experience. The paper objective is to overview of existing international forms and to rationale for promising forms and mechanisms of partnership with the local population in resolving the problems of solid domestic waste management. The paper proposes an authors’ view on establishing a partnership with the local population in resolving problems in management of solid domestic waste. A concise summary of the best world experience in attracting people to the garbage problem at the local and regional levels is worked it out. It is proposed to consider the key to an effective dialogue with the public through a prism of two fundamentally important issues: an attitude of the state and a society towards separate waste collection and a willingness to implement public-private partnerships. It is concluded that the public-private partnership mechanism is likely the most optimal in terms of sustainability for partnering with local communities. The examples presented in the article from the world experience of public participation show the dualism and dif culties in the practical realization of the right and desire of the population in solving the problems with solid waste. Ukrainian public organizations and local activists start to realize their bigger role in establishing a new quality of public-management relations in waste management and environmental education in particular. Due to foreign experience, one need to keep reshaping Ukrainian national waste management system based on high-tech solutions and wider engagement of socially responsible business. Perhaps public-private partnership  ts best as an optimal mechanism for this, being based on an achieved balance of interests, at least at the regional level. The presented from the world experience of public participation, proper examples show a dualism and dif culties in the practical realization of the population’s right and its desire to solve numerous problems with solid waste. It is impossible to establish partnership with the local population to solve «garbage problems» with no cohesion around simple value ideas. The sooner this happens, the more ecological and related problems with populism – at the national level as well as and with some unemployment and life expectancy locally, so it will ensure more healthy habitat for present and future generations.